Primary Structure and Conformation of a Tetrodotoxin-Binding Protein in the Hemolymph of Non-Toxic Shore Crab Hemigrapsus sanguineus - Yuji Nagashima; Kenta Fujimoto; Masahiko Okai; Yoichiro Kitani; Aya Yoshinaga-Kiriake; Shoichiro Ishizaki (Journal of Marine Science and Engineering, 2023)
Tetrodotoxin (TTX)-binding proteins are present in toxic TTX-bearing animals, such as pufferfish and gastropods. These may prevent autotoxicity. However, TTX-binding proteins are also found in the nontoxic marine shore crab, Hemigrapsus sanguineus. Here, we isolated the TTX-binding protein, HSTBP (Hemigrapsus sanguineus TTX-binding protein), from the hemolymph of H. sanguineus and elucidated its primary structure using cDNA cloning. HSTBP, a 400 kDa acidic glycoprotein by gel filtration high-performance liquid chromatography, comprises 3 subunits, 88 kDa (subunit-1), 65 kDa (subunit-2), and 26 kDa (subunit-3) via sodium dodecyl sulfate-polyacrylamide gel electrophoresis under reduced conditions. The open reading frame of the cDNA comprises 5049 base pairs encoding 1683 amino acid residues, and the mature protein contains 1650 amino acid residues from Arg34 to Ser1683. The three subunits are arranged in tandem in the following order: subunit-3 (Arg34-Gln261), subunit-1 (Asp262-Phe1138), and subunit-2 (Val1139-Ser1683). A BLAST homology search showed weak similarity of HSTBP to clotting proteins of crustaceans (29–40%). SMART analysis revealed a von Willebrand factor (vWF)-type (⇒delete hyphen) D domain at Phe1387-Gly1544. We confirmed that the recombinant protein of HSTBP subunit-2 containing the vWF-type (⇒delete hyphen) D domain bound to TTX at a molecular ratio of 1:1.